Strategi Pemasaran Kerajinan Aluminium Dengan Memanfaatkan Jaringan Sosial - Hesti Aulia Ningsih; Mery Yanti; Y Yunindyawati (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2018)
Basically, every business has a strategy in the business, the strategy used is to develop and maintain a business. The purpose of this study is to describe the condition of the business and marketing strategies aluminum craft by utilizing social networks at Desa Tanjung Atap Barat Kecamatan Tanjung Batu Kabupaten Ogan Ilir. The theory used is the social network theory from Wellman consisting of a bond, intensity, resources, distribution. The method used is descriptive qualitative. Sources of data derived from primary data through interviews and observations of the object of study and the secondary data obtained through documentation. The purposive technique used to determain informants aiming to get a lot of information related to the study. Data analysis techniques performed by several stages, such as data reduction, data presentation, and conclusion. The results of this study shows that for decades crafting aluminum has lasted for generations. The development of business in the past year experienced a drop in demand which resulted in a decrease in the amount of revenue of the business actors. Marketing strategies implemented by businesses actors is by using marketing mix known as 4P (product, price, promotion and place). Network used by businesses are aluminum craft labor, raw material suppliers, wholesalers, local government, transportation and consumer or customer. This network arose on the basis of kinship, friendship, know each other personally, trust, help each other, equality, same home and mutual need.